FACTORS AFFECTING SUCCESSFUL FROZEN EMBRYO TRANSFER IN CATTLE UNDER FARM CONDITION - MISHRA, G K; SINGH, NARINDER; SIDDIQUl, M U; SHUKLA, M K; SAXENA, S K (The Indian Journal of Animal Reproduction, 2023)
Embryo transfer technology (ETT) helps in tho dissemination of best germ plasm of both maleand female whereas artificial insemination {Al) disseminates only male genotype. The aim of presentstudy is to evaluate the variables affecting pregnancy rate following non-surgical embryo transfer incrossbred and indigenous cattle under farm condition. A total of 48 frozen embryos were transferredinto as many reciplents which resulted in overall 20.83 per cent pregnancy rate. The study revealedthat transfer of embryos into anterior one third of uterine horn resulted in significantly (P < 0.05) higherpregnancy rate (34.62%) compared to the posterior two third of uterine horn (4.55%). The resultsindicated that the site of embryo deposition in uterine horn has significant influence on the pregnancyrate in cattle.
Keywords: Frozen embryo transfer; Pregnancy; Cattle